HUBUNGAN KEHAMILAN GEMELI DENGAN KEJADIAN HIPERTENSI GESTASIONAL DAN KEJADIAN PERDARAHAN POSTPARTUM PRIMER - Haryati, Haryati; Kusmiyati, Yuni; Zein, Asmar Yetty (Poltekkes Kemenkes Yogyakarta, 2013)
Twin pregnancies is defined as pregnancy with two or more fetus. Twin pregnancies it can cause complications such as pregnancy induced hypotension and postpartum hemorrhage which is immediately of direct causes for maternal mortality. At RSUD Sleman twin pregnancies rate since 2009- 2011 are 89 (2,72%). Objective to determine the associated twin pregnancies with incident pregnancy induced hypertension and incidence postpartum hemorrhage primer of pregnancies women. Methods this study was observational analytic with historical cohort, using random sampling Teknik with sample 33 twins? pregnancies and 33 single lot pregnancy at RSUD Sleman Yogyakarta since 2009 - 2011. This analysis with univariate, bivariable, and multivariable. Result pregnancy induced hypertension was found to at develop 42,4% in the twin pregnancies, and 18,2% in the single pregnancy (P value 0,032). Women with twin pregnancies had higher rates of twin pregnancy induced hypertension (RR 3,32, 95% Cl 1,081 - 10,188). Postpartum hemorrhage primer was found to at develop 30,3% in the twin pregnancies, and 6,1%o in the single pregnancy. (P-value 0,011). Women with twin pregnancies had higher rates of postpartum hemorrhage primer (RR 6,74,95% Cl 1,346 - 33,75) Conclusion there was a significant associated twin pregnancies with incidence pregnancy induced hypertension and incidence, postpartum hemorrhage primer of pregnancies women.